2019
DOI: 10.1073/pnas.1800494116
|View full text |Cite
|
Sign up to set email alerts
|

E-protein regulatory network links TCR signaling to effector Treg cell differentiation

Abstract: T cell antigen receptor (TCR) signaling is essential for the differentiation and maintenance of effector regulatory T (Treg) cells. However, the contribution of individual TCR-dependent genes in Treg cells to the maintenance of immunotolerance remains largely unknown. Here we demonstrate that Treg cells lacking E protein undergo further differentiation into effector cells that exhibit high expression of effector Treg signature genes, including IRF4, ICOS, CD103, KLRG-1, and RORγt. E protein-deficient Treg cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Bcl-2 expression and increased cell death of these cells (23). In peripheral Tregs, recent gene expression analysis revealed loss of E proteins resulted in upregulation of proteins associated with proliferation and survival such as Bcl-2, Ki-67 and Bcl-11b (14). Here we showed that Id2 is a critical factor for the survival of aTregs and that loss of Id2 results in upregulation of the pro-apoptotic protein Fas.…”
Section: Cells Id2 Was Critical For Survival Of Hepatic Inkt Cells Amentioning
confidence: 50%
See 2 more Smart Citations
“…Bcl-2 expression and increased cell death of these cells (23). In peripheral Tregs, recent gene expression analysis revealed loss of E proteins resulted in upregulation of proteins associated with proliferation and survival such as Bcl-2, Ki-67 and Bcl-11b (14). Here we showed that Id2 is a critical factor for the survival of aTregs and that loss of Id2 results in upregulation of the pro-apoptotic protein Fas.…”
Section: Cells Id2 Was Critical For Survival Of Hepatic Inkt Cells Amentioning
confidence: 50%
“…However, the use of non-Treg specific Cre lines and a focus on analysis of the thymically-derived Treg populations, precluded significant advancement in understanding the function of these proteins in aTregs. More recently, E2A and HEB were shown to be critical for effector Tregs with Foxp3-Cre mediated loss of E proteins resulting in substantial increases in Tregs in peripheral tissues such as the small intestine, lung and liver, although the Treg population residing in adipose tissue was not examined (14). The function of Id2 and Id3 in conventional Tregs has also been examined by crossing Id2 and Id3 floxed animals to a Foxp3-Cre line (15).…”
Section: Detailed Gene Expression Analysis Of These Cells Revealed Thmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, Interferon Regulatory Factor 4 (IRF4), Myb, and Nuclear Factor Kappa-light-chain-enhancer of activated B cells (NF-κB) seem to kick-start the aTreg specification program [24][25][26][27], whereas Basic Leucine Zipper Transcription Factor (BATF), B-lymphocyte-induced maturation protein 1 (Blimp1), JunB, and Myb are then required to establish and maintain the aTreg landscape [24,28]. Importantly, negative regulators of the aTreg program have been described, such as Forkhead Box protein O (Foxo) or E-protein transcription factors [29,30]. At a more advanced level of differentiation, aTreg cells can acquire the expression of tissue-or microenvironment-induced transcription factors historically linked to the polarization of Tconv cells into Thelper (TH) subsets.…”
Section: An Overview Of Treg Cell Subsets and Their Transcriptional Rmentioning
confidence: 99%
“…E-proteins are transcriptional activators and repressors, the activity of which is inhibited by Id proteins. The E-proteins E2A and HEB inhibit the transition to the aTreg cell state [29]. Consequently, conditional ablation of E2A and HEB in mature Treg cells, leads to the accumulation of highly suppressive aTreg cells in the periphery [29].…”
Section: E-proteins and Their Inhibitor Of Dna Binding (Id) Counterpartsmentioning
confidence: 99%